Enhancement of photoluminescence signal from ultrathin layers with silicon nanocrystals - PEROVA, TANIA (My University, 2012)
Using the model of oscillating dipoles, we simulated the photoluminescence intensity of a triple-layered structure where the silicon nanocrystals layer was enclosed by buffer and capping silicon dioxide layers. It was found that a structure with an optimized buffer layer thickness exhibited photoluminescence which was approximately 20 times more intense than that from the structure without a buffer layer. Theoretical simulations were verified by photoluminescence measurements for the corresponding structures with silicon nanocrystals fabricated by plasma enhanced chemical vapour deposition.
PUBLISHED
Keywords: Buffer layers; Nanoscience & Materials